ETIKA BISNIS ISLAM: ISLAMIC CORPORATE GOVERNANCE DALAM MANAJEMEN OPERASIONAL DI INDUSTRI KREATIF: (Studi Kasus Pada Industri Kreatif UD. Snack Bu Ernie Lamongan) - Latifah, Eny; Nuriyah, Filza (Al-Musthofa: Journal of Sharia Economics, 2021)
The purpose of this study is to determine Islamic Corporate Governance with an Islamic business ethics approach in operational management implemented in UD's Creative Industries. Snack Mrs. Erni Lamongan. The research method used is descriptive qualitative with a case study type. The results of the study show that the Creative Industry Operations at UD. Snack Mrs. Erni Lamongan is inseparable from the implementation of Islamic Corporate Governance which is based on implementing the principles of Islamic business ethics including: Oneness (Tawhid), Balance or justice (Equiblirium), Free Will, Responsibility and Truth: Virtue, Honesty (Truth: Goodness, Honesty). Keywords: Islamic Business Ethics, Islamic Corporate Governance, Operational Management, Creative Industries.